Best friends forever - Weiner, Jennifer (Atria Books, 2009)
Popular television personality Valerie Adler turns to her long-forgotten, Illinois hometown friend Addie Downs when she runs into a bit of trouble involving betrayal and loyalty, family history and small-town secrets.